2013
DOI: 10.1021/nn4037859
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Physical and Biological Properties of Highly Fluorescent Aqueous Quantum Dots Using Block Copolymers of Different Size and Shape

Abstract: The phase transfer of fluorescent CdSe based quantum dots (QDs) while retaining their properties and offering some advantages concerning the stability and functionalization characteristics is an important and intensively investigated field of research. Here we report how to tune and control the properties of CdSe/CdS/ZnS core-shell-shell QDs in water, using poly(isoprene-block-ethylene oxide) (PI-b-PEO) as a versatile system of amphiphilic diblock copolymers for the micellular encapsulation of nanoparticles (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 56 publications
2
60
0
Order By: Relevance
“…9 was calculated from the integrated fluorescence intensity of the CdSe/ZnS QD alone, and the change in the fluorescence decay curve indicates evidence of the FRET process. 37 The time-resolved fluorescence intensity was fitted to a single exponential curve, and coefficients of determination (R 2 ) of the fitting functions were 0.99 for both the CdSe/ZnS QD alone and Fig. 7 The relationship of the pH to the ratio of emission intensities at 605 and 660 nm.…”
Section: Resultsmentioning
confidence: 99%
“…9 was calculated from the integrated fluorescence intensity of the CdSe/ZnS QD alone, and the change in the fluorescence decay curve indicates evidence of the FRET process. 37 The time-resolved fluorescence intensity was fitted to a single exponential curve, and coefficients of determination (R 2 ) of the fitting functions were 0.99 for both the CdSe/ZnS QD alone and Fig. 7 The relationship of the pH to the ratio of emission intensities at 605 and 660 nm.…”
Section: Resultsmentioning
confidence: 99%
“…213 In a subsequent report they detailed the synthesis of an amphiphilic miktoarm star copolymer made of two PEO and one PI chain, (PI-b-(PEO) 2 star), with control over the arm size via changes in the precursor molecular weights. 211 One of the key features of this polymer is its ability to provide an effective hydrophobic shielding around the nanocrystal surface, which drastically reduces diffusion/permeability of copper and iron ions to the QD surface. In particular, they showed that QDs encapsulated with an azide-modified block copolymer can be used to implement copper-catalyzed click reactions with minimal loss in the PL emission, circumventing previous limitations to using such coupling strategy when smaller surface ligands are used.…”
Section: Phase Transfer Via Encapsulation Within Amphiphilic Block Comentioning
confidence: 99%
“…36 Furthermore, a recent work has shown that coating of colloidal CdSe-based NCs with polymer shells with different permeability can be exploited to allow or to block cation exchange reactions. 39 In this work we demonstrate an approach for NC film patterning by locally inhibiting the cation exchange reaction via the exposure of the film to an electron beam or to an X-ray beam, as illustrated in Figure 1. NCs coated by native ligand molecules are homogeneously deposited on a substrate, as depicted in Figure 1a.…”
mentioning
confidence: 99%